2019
DOI: 10.1016/j.iotech.2019.11.003
|View full text |Cite|
|
Sign up to set email alerts
|

Tumour mutational burden: primary versus metastatic tissue creates systematic bias

Abstract: Tumour mutational burden (TMB) has emerged as a reproducible biomarker to predict immunotherapy response across multiple cancer types. However, a key aspect of TMB measurement that is often overlooked is the source of tissue sample used, which creates a potential for systematic bias. The predominant source is either primary or metastatic tumour tissue. Primary tumours are more heterogeneous and reflect a longer period of tumour evolution, whereas metastases tend to have a more monoclonal structure and potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
(58 reference statements)
4
16
0
Order By: Relevance
“…Studies have also shown that there is a significant difference in the TMB of primary and metastatic tumors from matched patients, indicating that there could be unique neoantigens present in different tumors from the same patient. 9 , 10 It is important to target all tumors within a patient to provide an optimal clinical response. Vaccine platforms commonly use in silico prediction methods to predict neoantigens that bind with high affinity to histocompatibility leukocyte antigens (HLAs) from the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that there is a significant difference in the TMB of primary and metastatic tumors from matched patients, indicating that there could be unique neoantigens present in different tumors from the same patient. 9 , 10 It is important to target all tumors within a patient to provide an optimal clinical response. Vaccine platforms commonly use in silico prediction methods to predict neoantigens that bind with high affinity to histocompatibility leukocyte antigens (HLAs) from the patients.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Moreover, tTMB measured from metastatic tumors are higher than that from primary tumors, but this is often overlooked when comparing bTMB and tTMB. 13 Tumor mutational burden and its measurement is increasingly being incorporated into routine practice to guide therapy in cancer patients. 9 However, there is a concern that immunotherapy can be used on patients inappropriately, especially since the concordance between bTMB and .…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 , 12 , 13 In line with our results, TMB has been shown to vary significantly between primary and metastatic sites in the same patient, with higher rates of TMB recorded in metastases than in primary tumor. 14 A study of NSCLC specimens presented an increase of TMB in metastatic specimens with the highest in BM samples with 13 Mut/Mb compared with 6 Mut/Mb in primary lung adenocarcinoma. In addition, further differences were identified in the NSCLC metastatic sites with brain and adrenal metastases showing the highest TMB, and bone and liver metastases, the lowest TMB across all metastatic sites.…”
Section: Discussionmentioning
confidence: 98%